The Impact of Annual Earnings Announcements on Convergence of Beliefs. - Brown, Lawrence D.; Han, Jerry C.Y. (The Accounting Review, 1992)
Abstract Examines the influence of annual earnings announcements on financial forecasts. Convergence of beliefs; Earnings surprise; Suggestion that annual earnings announcement should increase the convergence of analysts' forecasts of future earnings.